CHINESE-NESS AS A SPACE OF CONTESTATION: REREADING TWO INDONESIAN PERANAKAN MUSEUMS IN TANGERANG - Kurnia, Lilawati (UI Scholars Hub, 2023)
This paper discusses two museums that deliberately adopt the concept of “Peranakan” as part of their identities, namely the Museum Pustaka Peranakan Tionghoa, or the Peranakan Chinese Literature Museum (2012), and the Museum Benteng Heritage (November 11, 2011). Both are located in South Tangerang (ca.10 km from Jakarta). The term “Peranakan” indicates a mélange of identities for the Indonesian and Chinese. A closer examination of the Chinese in Indonesia reveals that during the New Order regime, the Indonesian Peranakan Chinese underwent a “repression” taking the form of various political policies and laws limiting their public roles, even attaching negative stigmas to the Chinese identity. The void space in state museums could be filled by these museums, which would demonstrate the endeavor to develop a fairer concept of nationhood. This paper is not intended to provide any solution to the current problem underlying the establishment of the museums. Rather, it is meant to explain the process that takes place when the identity of an ethnic group is questioned and politicized.